Pengaruh Soft Skill dan Hard Skill Tehadap Kesiapan Kerja Mahasiswa Melalui Motivasi Kerja Sebagai Variabel Intervening - Nugroho Dwi Prasetyo; Sutrisno; Heri Prabowo (Value Management Research, 2025)
This study aimed to analyze the influence of soft skills and hard skills as independent variables on work readiness, with work motivation serving as a mediating variable. The research was conducted on students of the Faculty of Economics and Business (FEB) at PGRI Semarang University from the 2023 cohort, which consisted of 315 individuals. A saturated sampling technique was used, meaning all 315 students were included in the study to ensure comprehensive and representative data. Data were collected using a structured questionnaire designed to measure the relationships between the variables of interest. The analytical method applied was the Structural Equation Model (SEM) using the Smart PLS 3.2.9 software to examine both direct and indirect relationships among the variables. This study aimed to provide a deeper understanding of how the development of both soft and hard skills impacts students’ readiness for entering the workforce and how work motivation plays a pivotal role in mediating these effects. The findings are anticipated to provide valuable insights for educational institutions, particularly in developing curriculum strategies that emphasize a balance between technical competencies and interpersonal abilities. Additionally, the study offers practical implications for creating targeted interventions and training programs to enhance students' motivation and readiness for employment. By identifying the key factors that influence work readiness, this research contributes to the growing body of knowledge on employability skills and provides actionable recommendations to better prepare students for their transition into professional environments.